Zoneamento geo-ambiental da parte ocidental do municipio de Quixeramobim-CE, com base em analise visual de imagens MSS, do Landsat - Oliveira, Vládia Pinto Vidal de (1989)
The present study was conducted with the objective to map the natural resources of the Quixerainobim county (Ceara State) western part; the used methodology v/as basèd on the general theory systems [...]